1986
DOI: 10.1029/ja091ia10p11337
|View full text |Cite
|
Sign up to set email alerts
|

Daytime high‐latitude rocket observations of the NO γ, δ, and ε bands

Abstract: Observations of the Earth's thermospheric dayglow were obtained on August 10, 1982, from Poker Flat, Alaska, using a rocket‐borne spectrometer covering the wavelength range 1950 to 2170 Å. This part of the spectrum is dominated by emissions from the gamma, delta and epsilon bands of nitric oxide. Column densities of nitric oxide were determined by fitting these bands with synthetic spectra. At low altitudes the (1, 0) and (2, 0) gamma bands exhibit large self‐absorption. Three bands of the weak NO epsilon syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 58 publications
4
39
0
Order By: Relevance
“…In laboratory measurements of the associative recombination process, only the v' = 0 level is populated [Groth et al, 1971], but if the results of Cleary [1986] are correct and fluorescence is the dominant daytime source of the S bands, then bands from higher v' levels may also be present.…”
Section: No 8 Bandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In laboratory measurements of the associative recombination process, only the v' = 0 level is populated [Groth et al, 1971], but if the results of Cleary [1986] are correct and fluorescence is the dominant daytime source of the S bands, then bands from higher v' levels may also be present.…”
Section: No 8 Bandsmentioning
confidence: 99%
“…Had Erwin filled Ihe (1,1) and (2,2) bands he would, in fact, have measured the degree of self-absorption of the (1,0) and (2,0) bands. Cleary [1986] derived altilude profiles of NO concenIralion from the j (1,0) and (2,0) bands. These profiles showed a roll over below 120 km, which the authors presumed to be due to self-absorplion.…”
Section: Introductionmentioning
confidence: 99%
“…The ions N + and O + are negligible, and correspond to less than 10% of the total absorption. We aim at showing the effect of the solar and geomagnetic activity on the NO excitation and ionisation [24]. shows that the state A 2 Σ + is one of the brightest in the Earth's atmosphere in general.…”
Section: Figs (3 4 5)mentioning
confidence: 99%
“…The fluorescence efficiency of the C state is low for v ϭ 0 and negligible for vϾ0, presumably due to rapid predissociation (9)(10)(11)(12). Day-time observations of the terrestrial atmosphere have found weak C 3 X (vЈ ϭ 0) bands, which have been attributed to resonance scattering (13)(14)(15), although there are significant uncertainties (16).…”
mentioning
confidence: 99%